2002
DOI: 10.1046/j.1525-1470.2002.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Skin Conditions in Primary School Children in Turkey: Differences Based on Socioeconomic Factors

Abstract: Skin diseases are associated with environmental factors and a public health approach is particularly important. We determined the prevalence of skin conditions and associated socioeconomic factors in primary school children in Turkey. A questionnaire for determining the socioeconomic level and a complete dermatologic examination were performed in 785 children in two primary schools in different socioeconomic areas of suburban and central Manisa, Turkey. The study included 345 (43.9%) girls and 440 (56.1%) boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
104
3
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 11 publications
18
104
3
6
Order By: Relevance
“…It was detected at a rate of 2.5% in a Spanish study (25); in a screening, performed in 7158 children between 6 and 14 years of age in Istanbul, the rate was detected to be 0.15 for T.Pedis (26); Balci et al reported a rate of 0.05 for T.Pedis in a screening of 8122 children (27). İnanir et al detected T. Pedis in 0.5 of 785 children (28).In our country, the rates in other studies range between 4.6 and 2.6% (11,18). In our study, we detected an overall rate of 0.35% in 72 children and a rate of 14% in the group for T. Pedis, similar to Tekin et al (29).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…It was detected at a rate of 2.5% in a Spanish study (25); in a screening, performed in 7158 children between 6 and 14 years of age in Istanbul, the rate was detected to be 0.15 for T.Pedis (26); Balci et al reported a rate of 0.05 for T.Pedis in a screening of 8122 children (27). İnanir et al detected T. Pedis in 0.5 of 785 children (28).In our country, the rates in other studies range between 4.6 and 2.6% (11,18). In our study, we detected an overall rate of 0.35% in 72 children and a rate of 14% in the group for T. Pedis, similar to Tekin et al (29).…”
Section: Discussionsupporting
confidence: 44%
“…In this study in 23235 children between 7 and 14 years, the ratio was detected to be 0.01% (26). The ratios were between 0.10 and 3% in the other studies in Turkey (12,13,26,28,31). Balci et al detected onychomycosis in a pediaric screening involving 8122 children between 5 and 16 years of age (0.018) (35).…”
Section: Discussionmentioning
confidence: 65%
“…Böylece prepubertal dönemde erkeklerde akne görülmezken, kızların küçük bir yüzdesinde pubertal döneme ait akne dışı bulgu yoktu. Bunun kızların pubertal gelişiminin erkeklere göre daha erken başlamasıyla ilişkili olduğu akla gelmektedir [19][20][21][22]28 . Pubertenin erken dönemlerindeki ve prepubertal dönemdeki akne, yerleşim yeri, akne lezyonlarının tipi ve tedavideki farklılıklarıyla adolesan dönemde görülen akneden bazı farklılıklar göstermektedir.…”
Section: Discussionunclassified
“…İnanır et al investigated the relation of skin diseases with socioeconomic factors in children [4]. Serarslan et al evaluated the prevalence of skin diseases in children and adolescents living in orphanages in Antakya [5].…”
Section: Introductionmentioning
confidence: 99%